Formação do enfermeiro docente na pós-graduação : percepções de egressos de um mestrado acadêmico - Corrêa, Ludmilla Zangali de Mattos (2013)
Teacher education in higher education , specifically training for school nurses , is the central theme of this study. Aimed to analyze the formation of nursing teachers for higher education from the perspective of graduates from an academic master's degree in nursing. This is a descriptive exploratory qualitative research conducted with eight nurses graduates of the course academic Master's in Nursing from a Federal University of midwestern region of Brazil , the classes of 2008 and 2009 and engaged in teaching in higher level . Data were collected from November 2012 to February 2013, through semi-structured interview. The interviews were audio recorded and transcribed . The data were subjected to the technique of content analysis of the thematic , organized and summarized in type topics . This research is part of a matrix project approved by the Research Ethics Committee of the Julio Muller University Hospital , under the protocol number No. 798/CEP-HUJM/10 . The results were organized into three topics : a) Form to be " teacher " and " being a researcher " - realize these two dimensions of formation from two perspectives : disarticulated and articulated b ) curricular strategies in academic master nursing - refers steps / phases fulfilled according to curriculum organization , reporting to the following structures provided in the course: the disciplines , the stage of teaching , participation in the activities of the research group including meetings related to research projects and coorientações of the course students graduation c ) the ethicalpolitical dimension in the training of teaching nurses - aspects which include the example of teachers , training in interpersonal relationships , the politics stimulation , creativity and reflective attitude to practice. The perspective that best represents the look for the formation of nursing teachers is to " researchers " and " teacher " in an integrated and complementary perspective with a broader sense of the scope of the course . The concern with training would be based on the intention to make prevail the view that education is not only the transmission of already formulated knowledge and research enables teachers to take up work with students who cause the formulation of new knowledge or questioning the existing , and which fosters skills related to the position on knowledge and social reality . The ethical- political dimension of training for school nurses shows that teaching is a complex activity and requires a careful preparation for the exercise . This ethical sensitivity in the speeches of the graduates regarding values such as commitment to learning from each other , show that this training does not always convert into goals , but even so can no longer be promoted both in teacher training process , as in professional practice , they are phenomena that involve human condition and values related to caring, autonomy and political nature in the teaching- learning process and the formation of critical and reflective practitioners .